2003
DOI: 10.1207/s15327914nc4502_14
|View full text |Cite
|
Sign up to set email alerts
|

Role of Caspase-8 Activation in Mediating Vitamin E-Induced Apoptosis in Murine Mammary Cancer Cells

Abstract: The vitamin E family of compounds is divided into two subgroups, tocopherols and tocotrienols. However, tocotrienols display more potent apoptotic activity in mammary cancer cells. Although the mechanism(s) mediating tocotrienol-induced apoptosis is presently unknown, apoptosis is carried out by activation of initiator caspases (caspase-8 or -9) that subsequently activate effector caspases (caspase-3, -6, or -7). Studies were conducted to determine whether tocotrienol-induced apoptosis is mediated by activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
125
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(129 citation statements)
references
References 41 publications
3
125
1
Order By: Relevance
“…Our data are in agreement with other published reports that tocotrienol is a superior molecule among the members of the family of vitamin E (88,92,93). Four different homologues of tocotrienols have been identified, viz.…”
Section: Discussionsupporting
confidence: 93%
“…Our data are in agreement with other published reports that tocotrienol is a superior molecule among the members of the family of vitamin E (88,92,93). Four different homologues of tocotrienols have been identified, viz.…”
Section: Discussionsupporting
confidence: 93%
“…It considered as the central function in caspase cascade regulation and induction of apoptosis (Shafi et al, 2009). It has been found that caspases are the most important molecules in the apoptotic process which they enhance the pathway of the apoptotic cascade (Shah et al, 2003). This pathway is starting with releasing the cytochrome-c from the mitochondrial cells which stimulate the procaspase-9 and caspase-3 expression (Shafi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…35 The anticancer effect of T3 was found to be mediated through antiproliferation, 16,36,37 induction of apoptosis, 38,39 cell cycle arrest, 13,40 antiangiogenesis 41 and antiinvasion. 18 More recently, c-T3, one of the four isoforms of T3, was reported to possess chemosensitizing effects, 17,18 which led us to speculate that c-T3 may be able to target the chemoresistant cancer stem-like cells.…”
Section: Discussionmentioning
confidence: 99%